A STUDY ON DEPRESSION AND COGNITIVE DISTORTION AMONG OUT-OF-WEDLOCK PREGNANT YOUNG WOMEN IN MALAYSIA (Jurnal Kemanusiaan, 2022)
The percentage of out-of-wedlock pregnancies increases dramatically every year. This matter needs to be taken into account as it results in negative effects, especially from a mental and emotional point of view which can ultimately affect the human capital of the country. This study aims to identify the level of depression and cognitive distortion among out-of-wedlock pregnant young women. This study used quantitative methods of collecting data in which the Beck Depression Inventory for Malays (BDI-Malay) and the Inventory of Cognitive Distortion (ICD) questionnaires were distributed to respondents. A total of 70 out-of-wedlock pregnant young women who were in nine shelters across the country had participated in this study. The results show that depression was at a mild level and cognitive distortion was at a moderate level. In addition, the levels for the dimensions of depression namely cognitive/affective and somatic/vegetative as well as the dimensions of cognitive distortion namely externalization of self-worth, fortune telling, selective abstraction, dichotomous thinking, magnification, minimization, perfectionism, comparison to others, emotional reasoning, arbitrary inference, and personalization were also obtained. The study also found a significant positive linear relationship between depression and cognitive distortion (r = 0.578, p